The reality of the problems of teaching performance of middle school physical education and sports teachers from their point of view - Seghir , noureddine; abbou, soufiane (sports creativity, 2024)
THE STUDY AIMED TO SHED LIGHT ON THE DEGREE OF IMPACT OF SOME OF THE PROBLEMS THAT HINDER THE TEACHING PERFORMANCE OF TEACHERS OF PHYSICAL EDUCATION AND SPORTS IN THE INTERMEDIATE STAGE. THE RESULTS VARIED BETWEEN EACH OF THE STUDY AXES IN A MEDIUM TO HIGH DEGREE, ACCORDING TO THE RESEARCH SAMPLE RESPONSES